An Evaluation Study on the Transparency of Secondary Education Financing Based on the Discrepancy Model (Provus) - Arlen Orlando Lukas; Nurhattati Fuad; Rugaiyah (Didaktika: Jurnal Kependidikan, 2025)
This study aims to evaluate the transparency of educational financing at SMPN 203 Jakarta by focusing on information availability, public involvement, accessibility, financial reporting, internal monitoring, and external auditing, using the Discrepancy Evaluation Model (Provus). A qualitative research approach was employed, involving 15 purposively selected participants comprising internal school stakeholders and external auditors. The findings reveal that the availability of financial information remains limited to offline formats, lacking support from digital platforms. Public involvement is primarily consultative, with restricted participation from the school committee and class coordinators. Information accessibility is suboptimal due to the absence of a digital information system. Financial reporting complies with existing regulations, internal monitoring is conducted by a designated team through regular inspections, and external audits are effectively carried out by the Regional Education Office II of East Jakarta and the Education Department. The implications of this study underscore the need to develop a digital information system and enhance public participation to bridge the transparency gaps identified. Furthermore, it emphasizes the importance of strengthening accountable and sustainable financial governance in education. These findings offer significant contributions to the theoretical and practical development of educational financing transparency in secondary schools.